2009
DOI: 10.1038/emboj.2009.285
|View full text |Cite
|
Sign up to set email alerts
|

The kinase TNIK is an essential activator of Wnt target genes

Abstract: Wnt signalling maintains the undifferentiated state of intestinal crypt/progenitor cells through the TCF4/b-catenin-activating transcriptional complex. In colorectal cancer, activating mutations in Wnt pathway components lead to inappropriate activation of the TCF4/b-catenin transcriptional programme and tumourigenesis. The mechanisms by which TCF4/b-catenin activate key target genes are not well understood. Using a proteomics approach, we identified Tnik, a member of the germinal centre kinase family as a Tcf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
205
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(221 citation statements)
references
References 30 publications
14
205
2
Order By: Relevance
“…In fact, undifferentiated cells at the bottom of the intestinal crypts accumulate nuclear β-catenin (41). Mahmoudi and colleagues showed that TNIK interacted with and phosphorylated β-catenin as well as TCF4 (21). We further showed that TNIK phosphorylated the S154 residue of TCF4 ( Fig.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In fact, undifferentiated cells at the bottom of the intestinal crypts accumulate nuclear β-catenin (41). Mahmoudi and colleagues showed that TNIK interacted with and phosphorylated β-catenin as well as TCF4 (21). We further showed that TNIK phosphorylated the S154 residue of TCF4 ( Fig.…”
Section: Discussionsupporting
confidence: 63%
“…Here, we report that colorectal cancer cells are highly dependent on the expression and kinase activity of TNIK for proliferation in vitro and in vivo. During the preparation of this article, Mahmoudi and colleagues also identified Tnik as a protein interacting with Tcf4 in the mouse intestinal crypt (21). Their data overlapped partly with ours: TNIK is an activating kinase for the TCF4 and β-catenin transcriptional complex.…”
Section: Introductionsupporting
confidence: 57%
“…This hypothesis is consistent with the aforementioned finding that the interaction of NFAT with Dvl is induced by Ca 2ϩ signals in the nucleus. To test this hypothesis, LS174T cells that contain oncogenic mutation of ␤-catenin gene (37,38) and Caco-2 or SW480 cells which contain mutated adenomatous polyposis coli (APC) (39) were used to examine the effect of Ca 2ϩ signaling/NFAT on Wnt reporter activity. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Coimmunoprecipitation was carried out as previously described (53). In short, mouse primary crypt material was prepared as described above for Western blot and qRT-PCR of intestine, and then prepared in PLB buffer (1% Triton X-100, 2 mM EDTA, 1 mM DTT, 5% glycerol in PBS) supplemented with complete protease inhibitor cocktail (Sigma-Aldrich).…”
Section: Discussionmentioning
confidence: 99%